2017
DOI: 10.1016/j.athoracsur.2017.01.058
|View full text |Cite
|
Sign up to set email alerts
|

How to Perform a Late Surgical Explantation of a CoreValve Aortic Bioprothesis

Abstract: As transcatheter techniques expand to younger patients, cardiac surgeons need to know a safe surgical technique to extract these kinds of prostheses. We describe here an adequate surgical strategy for the explantation of a CoreValve prosthesis that was implanted more than 5 years previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…Our group recently described an adequate surgical technique to explant TAVI-placed prostheses [1]. In this report, we have provided videos demonstrating the ease of the endarterectomy, and we confirmed that there were no adhesions at the coronary ostia, thereby facilitating explantation of the prosthesis without the need for aortic root replacement.…”
Section: Commentsupporting
confidence: 57%
See 2 more Smart Citations
“…Our group recently described an adequate surgical technique to explant TAVI-placed prostheses [1]. In this report, we have provided videos demonstrating the ease of the endarterectomy, and we confirmed that there were no adhesions at the coronary ostia, thereby facilitating explantation of the prosthesis without the need for aortic root replacement.…”
Section: Commentsupporting
confidence: 57%
“…Therefore, it would be very helpful to know a safe and easy way to perform it. We have described a surgical technique for this operation [1]. In this report we show that this technique can be used routinely, and we provide videos of the operation.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…There have been several techniques to explant TAVR prosthesis safely and effectively, avoiding aortic root injury. Hernandez-Vaquero et al [ 3 , 4 ] used an endarterectomy spatula for meticulous dissection and Valdis et al [ 5 ] used a heavy snaring suture to collapse the prosthesis and facilitate explantation. To create a better surgical field for meticulous dissection, we used 2 consecutive 2–0 polyester snaring sutures, which were fastened by tourniquets.…”
Section: Discussionmentioning
confidence: 99%